Evaluation of Crash Tests of the Institute of Forensic Engineering, University of Zilina, Aimed at EES - Pavol Kohut; Gustav Kasanicky (Communications - Scientific letters of the University of Zilina, 2013)
For the proper analysis of traffic accidents it is important to properly evaluate the deformation work of a vehicle deformation based on the extent of damage of the vehicle. The Institute of Forensic Engineering, University of Zilina, made a series of vehicles crash tests focused on the evaluation of the vehicle deformation work. The article focuses the on evaluation of the vehicle deformation work or of the EES (energy equivalent speed) and comparison of stiffness tests of cars (production year around 2000) and older generation of vehicles (which were subject of tests - Crash tests DSD LINZ 1996).